2015
DOI: 10.2310/7750.2014.14106
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Cutaneous Creamy Papules and Nodules: A Case of Miliarial Gout

Abstract: Miliarial gout is a rare form of cutaneous tophaceous gout that is treated using xanthine oxidase inhibitors such as allopurinol and febuxostat or uricosurics such as probenecid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 7 publications
2
17
0
Order By: Relevance
“…In some instances, the term miliarial gout has been used to describe cases featuring diffuse milialike papules [3]. Given its varied clinical morphologies, the differential diagnosis can also include calcinosis cutis, rheumatoid nodules, foreign body granulomas, and eruptive xanthomas [4]. The pathogenesis is poorly understood.…”
Section: Case Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some instances, the term miliarial gout has been used to describe cases featuring diffuse milialike papules [3]. Given its varied clinical morphologies, the differential diagnosis can also include calcinosis cutis, rheumatoid nodules, foreign body granulomas, and eruptive xanthomas [4]. The pathogenesis is poorly understood.…”
Section: Case Discussionmentioning
confidence: 99%
“…The pathogenesis is poorly understood. In our review of 23 reported cases of extensive extra-articular dermal/subcutaneous tophi (including the present case), [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18], the majority of patients were male (87%) and Asian (57%), (Table 1). There was fairly equal representation from Asian countries with high gout prevalence (Taiwan) as well as those with low prevalence (China, South Korea, Philippines, Vietnam), [19].…”
Section: Case Discussionmentioning
confidence: 99%
“…Tophaceous gout can present with varied cutaneous manifestations including papular, nodular, ulcerative, and pustular forms. [ 2 ] The nodules can be firm, smooth or multilobulated and are situated in the subcutaneous plane. [ 3 ] The 3 different stages of gout, which may be seen after years of asymptomatic hyperuricemia, are acute gouty arthritis; intercritical gout, which includes the intervals between attacks; and chronic tophaceous gout.…”
Section: Discussionmentioning
confidence: 99%
“…Acute inflammatory attacks are managed with colchicine and non-steroidal anti-inflammatory drugs. [ 2 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation